Розробка компонентів інформаційної системи для створення музики - Романюк, А. С. (ХНУРЕ, 2024)
This project focuses on developing an information system dedicated to music creation, emphasizing its significance in the contemporary landscape. A comprehensive analysis of existing counterparts has been conducted to discern the unique attributes of the proposed application. A thorough comparison of the advantages and drawbacks of the system has been performed. The target audience for this platform has been identified, shedding light on the specific demographic it aims to serve. The distinctive features that set this system apart from others in the market have been outlined, highlighting its competitive edge. Delving into the intricacies of information systems, the core components integral to the functionality of this application have been thoroughly examined. Through this, a comprehensive understanding of how the system operates and caters to the needs of its users has been established, solidifying its role in the realm of music creation.
Keywords: music creation; створення музики